Accurate solution of the volume integral equation for high-permittivity scatterers. - Kottmann, J.P.
We present a formalism based on the method of moment to solve the volume integral equation using tetrahedral (3-D) and triangular (2-D) elements. We introduce a regularization scheme to handle the strong singularity of the Green's tensor. This regularization scheme is extended to neighboring elements, which dramatically improves the accuracy and the convergence of the technique. Scattering by high-permittivity scatterers, like semiconductors, can be accurately computed. Furthermore, plasmon-polariton resonances in dispersive materials can also be reproduced
Keywords: 2D elements; 3D elements; Green's tensor; Accurate solution; Convergence; Dispersive materials; High-permittivity scatterers; Method of moment; Plasmon-polariton resonances; Regularization scheme; Semiconductors; Singularity; Tetrahedral elements; Triangular elements; Volume integral equation